Cloning, Expression and Bioinformatic Analysis of Human Papillomavirus Type 52 L1 Capsid Gene from Indonesian Patient - SONY SUHANDONO; DEWI AYU KENCANA UNGU; TATI KRISTIANTI; EDHYANA SAHIRATMADJA; HERMAN SUSANTO (Indonesian Society for microbiology, 2014)
Human papillomavirus (HPV) type 52 is the most prevalent type for causing cervical cancer in Indonesian population. Cervical cancer becomes the most common cancer suffered by Indonesian women. Prevention of HPV infection can be achieved using HPV virus-like particle (VLP) vaccine derived from L1 major capsid protein. Â This study aimed to clone and analyze HPV-52 L1 gene. DNA obtained from biopsy of a cervical cancer patient was amplified using specific primers designed from Asian originated HPV-52 L1 gene available in the GenBank. The isolated HPV-52 L1 gene sequence was submitted to GenBank with accession number [KF225497]. Expression of HPV-52 L1 gene was performed using pRSET/EmGFPEscherichia coli expression vector. We analyzed and compared the HPV-52 L1 gene expressions from recombinant E.coli BL21 (DE3) that had been induced for 3 hours with 1 mM IPTG and without induction. The protein was expressed in insoluble form. We performed the following bioinformatic analyses: construction of phlyogenetic tree, T-cell epitopes prediction and 3D proteins structure modelling. We utilized the following softwares: MEGA5 for phylogenetic tree, IEDBann for MHC prediction, CLC DNA Workbench 6.5 for hydrophobicity analysis and PDB-Viewer Deep for 3D protein structure analysis. The phylogenetic tree which was developed based on [KF225497] sequence showed that it shared a branch with Asian countries (Philippines and Thailand). The deduced amino acid sequences of the predicted epitopes that were consistent in all of the programs were 259GTLGDPVPGDLYIQGS274 and 345KKESTYKNE353. This information may be useful to design diagnostic strategies and vaccine suitable for Indonesian population.